Cloud processing of security events for VANET distributed sensors. Issue 1 (March 2021) - Bolodurina, I P; Ushakov, Y A; Parfenov, D I; Cui, J
Abstract: Machine-to-machine communication networks, which are related to human activities, are today one of the fastest growing IT sectors. The most vulnerable in terms of security is the Internet of Things and VANET segments. When devices interact, various types of targeted attacks are possible, as well as failures or random dangerous events. The handling and response to security events, in this case, must be fast. However, the specificity of VANET networks does not allow the use of classical intrusion prevention systems due to the constant movement between connection points, for example, in LTE or 5G networks. The article is devoted to the possibility of quickly deploying a cluster of security events analysis based on containerization on existing virtual machines that are closest to the event source. The analysis of the scaling speed, as well as the performance limits of event processing processes on various configurations of the data analysis cluster.